Impact of Factional Differences within the Afghan Taliban on the China-Pakistan Economic Corridor (Journal of Interdisciplinary Insights, 2024)
In August 2021, the Afghan Taliban made a comeback and regained power in Afghanistan. The Atta organization has always shown a united image to the outside world, but since the Atta regained power so far, the differences between the factions within the Atta have gradually emerged, and the factions have fallen out with each other due to power struggles and resource grabbing, which has seriously impeded the development of Afghanistan and caused the spillover of the terrorist organization's power. The China-Pakistan Economic Corridor (CPEC), as the flagship project of the Belt and Road Initiative (BRI), promotes the common development of China and Pakistan and witnesses the establishment of friendship between the two countries. As a neighboring country of Afghanistan, the internal factional differences of Atta organization will affect Pakistan's internal security and stability, meanwhile, these will hinder the construction and development of the China-Pakistan Economic Corridor.